2018
DOI: 10.1002/mar.21132
|View full text |Cite
|
Sign up to set email alerts
|

Tell me your story and I will tell you who you are: Persona perspective in sustainable consumption

Abstract: Although research in marketing and consumer behavior has tried to portray sustainable consumers in many different ways, a clear, consistent, and granular identification of these consumers is still not available due to the complexity of sustainable consumption. This study adopts personas as a way to better explain and understand the holistic nature and complexity of sustainable consumer behavior in terms of its various stages (i.e. acquisition, usage, and postuse) within four key behavioral functions of mobilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 69 publications
1
29
0
Order By: Relevance
“…The preponderance of intra‐domain (positive) behavioral effects or spillovers (e.g., within the transport and home energy domains) may be indicative of different groups of individuals with varying levels of environmental engagement. There is evidence that, for some people, environmental friendliness stretches across all (or most) facets of behavior, whereas other people restrict their environmental efforts to specific (easier or especially relevant) action domains (Iyer & Muncy, ; Onel et al, ). In line with self‐perception theory, inter‐domain spillovers among EOA actions are likely to depend on personal characteristics (e.g., an environmental self‐identity) that transcend specific behavioral domains (Lauren et al, )—and that fall beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preponderance of intra‐domain (positive) behavioral effects or spillovers (e.g., within the transport and home energy domains) may be indicative of different groups of individuals with varying levels of environmental engagement. There is evidence that, for some people, environmental friendliness stretches across all (or most) facets of behavior, whereas other people restrict their environmental efforts to specific (easier or especially relevant) action domains (Iyer & Muncy, ; Onel et al, ). In line with self‐perception theory, inter‐domain spillovers among EOA actions are likely to depend on personal characteristics (e.g., an environmental self‐identity) that transcend specific behavioral domains (Lauren et al, )—and that fall beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the extant literature on anticonsumption lifestyles shows that some people consistently engage in EOA behaviors (Iyer & Muncy, ). For such individuals, EOA becomes a key component of their personal identities and roles (Black & Cherrier, ), and lead to greater engagement levels in EOA actions across settings or domains (Onel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, their research, focused on software development, provides no empirical results. Onel et al (2018) used personas to understand consumer behavior regarding sustainable consumption, finding three different consumer archetypes with distinct sustainable consumption strategies. Al-Qirim (2006) used personas to investigate e-commerce adoption in small businesses in New Zealand.…”
Section: Related Literaturementioning
confidence: 99%
“…Drawing on signaling theory, Brach, Walsh, and Shaw [8] showed that third-party certification labels on sustainable products provide brand-like information cues that reduce the perceived risk of sustainable products, but consumers must perceive them as credible to have their risk perceptions reduced. Onel et al [9] adopted personas as a way to better explain and understand the holistic nature and complexity of sustainable consumer behavior in terms of its various stages (i.e., acquisition, usage, and post-use) within key behavioral functions of mobility, housing, clothing, and food. Sustainable consumption is associated with the reduction of food waste [10] and eating organic food [11][12][13] and local food [14], among other activities.…”
Section: Introductionmentioning
confidence: 99%